Praktik Repacking Beras Berkualitas Rendah sebagai Beras Medium dalam Perspektif Fikih Muamalah Ibnu Taimiyah: Studi Kasus di Kecamatan Sail, Pekanbaru - Lubis, Mhd Al Dauri; Muhibbussabry, Muhibbussabry (AL-SULTHANIYAH, 2026)
The rice trade in traditional markets still faces issues of inconsistency between the quality of rice and the information stated on the packaging, one of which occurs through the practice of repackaging low-quality rice and selling it as medium or premium rice. This study aims to analyze the practice of repackaging (repacking) medium rice using low-quality rice in traditional markets in Pekanbaru from the perspective of Indonesian positive law and Islamic economic principles. This research employs a qualitative approach through interviews, observations, and documentation. The findings indicate that the repacking practice causes losses for consumers because the quality of the rice does not match the information provided on the packaging and may also pose potential health risks. From a legal perspective, such actions violate Law Number 8 of 1999 concerning Consumer Protection and regulations related to food labeling. However, weak supervision has allowed this practice to continue without adequate enforcement. From the perspective of Islamic economics, the repackaging of low-quality rice that is sold as medium or premium rice constitutes tadlis (deception) and gharar (uncertainty), which contradict the principles of honesty, trustworthiness, and fairness in transactions. The concept of hisbah in the thought of Ibn Taymiyyah emphasizes the obligation of the state to supervise markets and prevent fraud. Nevertheless, the conditions in the field indicate that this function has not yet been carried out optimally. This study highlights the importance of strengthening government supervision and improving consumer literacy. It also contributes academically by enriching studies on fraudulent practices in food trade through the integration of Indonesian positive law analysis and Islamic economic perspectives, particularly the concept of hisbah in Ibn Taymiyyah’s thought as a mechanism for market supervision.